ANALISIS KINERJA JARINGAN WI-FI PADA BAWASLU DENGAN METODE NETWORK DEVELOPMENT LIFE CYCLE (NDLC) - Nengsi Selfiana Ndun; Yohanes Suban Belutowe (Lembaga Pengembangan Kinerja Dosen, 2025)
In the era of digitalization, Wi-Fi networks have become an essential need for government agencies, including the General Elections Supervisory Agency. This study aims to analyze the performance of the Wi-Fi network at the BAWASLU Office in East Nusa Tenggara using Quality of Service (QoS) parameters such as throughput, delay, and packet loss, with the Network Development Life Cycle (NDLC) method approach. Data were collected through observation, interviews, and literature studies. The test results showed that the performance of the Wi-Fi network was measured in varying categories depending on the parameters tested. Factors such as the number of users, the physical condition of the building, and device configuration affect the quality of network services. Based on the analysis, this study provides recommendations for optimizing network performance, including increasing bandwidth capacity and setting traffic management. This study is expected to be a reference for network management in other government agencies.